Technical note: Spectral slopes in a deep, weakly stratified ocean and coupling between sub-mesoscale motion and small-scale mechanisms - H. van Haren (Ocean Science)
Large, basin-wide ocean circulations are complex non-linear dynamical systems. They include small-scale physical processes such as transport by sub-mesoscale eddies and turbulence-generating breaking of internal waves. To date, however, knowledge is lacking on the precise interactions between the different processes. In this note, a potential contributor to the interactions is investigated using spectra from deep-sea-moored observations. In weakly stratified waters, continuous spectral slopes are observed that extend from sub-mesoscales across the internal wave band to the turbulence range. In the latter, the governing slope can be distinctly different from the inertial subrange of shear turbulence and is described as the buoyancy subrange of convection turbulence. At sub-inertial frequencies, the slope's extension describes either quasi-gyroscopic waves or sub-mesoscale eddies. Such cross-spectral correspondence suggests a potential feedback mechanism stabilizing large-scale ocean circulations.